Spleen, Non-Systemic Diffuse Lymphangiomatosis - Majid, Sarosh; Zaman, Samina; Anwar, Ambreen; Chughtai, Omer (International Journal of Pathology, 2018)
Lymphangiomatosisis a rare disorder believed to be result from a developmental malformation oflymphatic system. Lymphangiomatosis involves bone, soft tissues, and viscera in a diffuse fashion. Wedescribe an unusual case of splenic lymphangiomatosis in 41 years old female.